IOT BASED STREET LIGHT INTENSITY CONTROLLING USING POWER ELECTRONICS - P.Nagaveni, A.Nagaraj, M.Nagaraj (International Journal of Advanced Science and Technology, 2020)
Exhaustion of the worldwide fossil-vitality sources was going quick, so the improvement of sustainable power source is the must required and best arrangement. In any case, the accessible sustainable power sources, for example, wind, sunlight based, and energy components are dependent on the climate conditions, and their yield voltages are low and variable. So we should limit our vitality utilization as conceivable Here we propose a framework utilizing detecting the development the sensor transmit the information to the microcontroller which besides the Light to turn ON. Correspondingly when the vehicle or an obstruction leaves the Light gets turned OFF as the sensor sense any item simultaneously the status(ON/OFF) of the road light can be gotten to from anyplace and whenever through web. The voltage devoured by the framework is additionally checked remotely.